Videofeedback and video modeling: effects of both procedures in mother’s behavior changes (Brazilian Journal of Behavioral and Cognitive Therapy, 2007)
The objective of this work is to compare results of the use of videofeedback and video modeling procedures in parent training of preschool children about the agility to produce changes in behaviors related to the use of the diferencial reinforcement (to increase the positive attention to appropriate behaviors and to decrease the negative attention and punishment to inadequate behaviors). Two dyad mother-child participated. The children had three and four years, with externalizing and internalizing behavior problems, respectively. The procedure consisted of training the mothers, alternating the procedure of videofeedback and video modeling, making repeated measured observations between the sessions. In the two cases, the video modeling presented superior results, which demonstrated that watching a proficient therapist giving model of the target-skills to the mother is relevant to perception the immediate changes in the child’s behavior in function of simple changes in the interaction patterns.